2012
DOI: 10.4236/jmmce.2012.1110100
|View full text |Cite
|
Sign up to set email alerts
|

FEM Simulation and Experimental Validation of Cold Forging Behavior of LM6 Base Metal Matrix Composites

Abstract: The present paper examines the deformation behavior of solid cylinders of an aluminium alloy metal matrix composite (MMC) undergoing axial compression in a Universal Testing Machine under dry condition. The composite was prepared by the stir casting method from LM6 aluminium alloy using silicon carbide particles (SiC) as reinforcing agent. The effect of weight percentage of silicon carbide on microstructure, hardness and upsetting load is studied. The friction factor at die metal interface is evaluated by ring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Rozovsky, Hahn, and Avitzur (1973) reported that the compression of a short cylinder between anvils is a much better test for metal working applications. The deformation behavior of solid cylinders of an aluminum alloy metal matrix composite under dry condition was estimated by Joardar, Sutradhar, and Das (2012). It was reported that a cylindrical preform can be successfully compressed to a height reduction by 28-32% without fracture.…”
Section: Introductionmentioning
confidence: 99%
“…Rozovsky, Hahn, and Avitzur (1973) reported that the compression of a short cylinder between anvils is a much better test for metal working applications. The deformation behavior of solid cylinders of an aluminum alloy metal matrix composite under dry condition was estimated by Joardar, Sutradhar, and Das (2012). It was reported that a cylindrical preform can be successfully compressed to a height reduction by 28-32% without fracture.…”
Section: Introductionmentioning
confidence: 99%
“…The equations are arrived and comparison between the theoretical and experimental values is done. Hillol Joardar et al [4] studied to estimate the results of assail particle on the microstructure associate degreed mechanical performance of associate degree metallic element alloy composite (LM6/SiC) created by stir casting. The experimental results unit finally compared with those obtained by finite half simulation.…”
Section: Introductionmentioning
confidence: 99%
“…The silicon based aluminium alloy A413, which was chosen for this work, is associated with the theoretical density of 2.66 g/cm 3 . This alloy has been selected because of its good fluidity due to the presence of silicon content [1][2][3][4][5]. Also it is associated with excellent pressure tightness, good hot tear resistance, good castability, good machinability, high specific strength, and high corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%